Flood Prone Area Analysis using Landsat 9 and MCDA Method in Bekasi Regency - Zahra Putri Callibri Suharyanto; Filsa Bioresita (Institut Teknologi Sepuluh Nopember, 2025)
Mapping reveals Bekasi (total 126,266.77 ha) has four flood vulnerability classes. Most land (68.5% or 86,454.87 ha) is Medium risk, primarily in transitional zones prone to inundation from extreme rain or land-use changes. High-risk areas cover 21,831.52 ha, while Low-risk zones span 17,980.39 ha. This distribution shows the regency is predominantly moderate-to-highly vulnerable, driven by lowland topography and proximity to rivers. As West Java's most flood-damaged region in the past decade, a study integrated Landsat 9 imagery and MCDA to map flood risk using five parameters (land cover, elevation, rainfall, soil, river buffers). Validated with BNPB historical data, the model confirmed northern areas (Tambun, Muara Gembong, Babelan) as highest risk due to low elevation (<10 m), alluvial soil, and frequent flooding.